URGENSI PENUNJUKAN ARBITER OLEH KETUA PENGADILAN NEGERI DALAM PROSES ARBITRASE - Zuhairi Bharata Ashbahi (Program Magister Hukum Universitas Lambung Mangkurat, 2016)
Arbitrators have very important role in the process of dispute settlement through arbitral institusion. Therefore, Act number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution regulates the procedure of the appointment of an arbitrators in case of dispute among the parties. The Chairman of District Court is given the authority by the act to resolve the disputes on the appointment of arbitrators, both disputes in as ad hoc arbitration and institusional arbitration. Nonetheles, it is qustionable and the aothority on the settlement of disputes concerning the appointment aof the arbitrators given by the act to the Chairman of district court. Its is also because the spirit which is expented to be built from the disputes settlement is the late process as a result of the procedural and administrative factors can be avoided. Besides, is the authority in accordance with the principle of simple, quick and inexpensie trial. It wil not become simple because the forum must be moved. It will not become quick because it still take time to settle it and it will requires costs for the trial at the court. In addition to, the Chairman of District Court should have the certain criteria in appointing arbitrators because the requirements stipulated in Article 2 or Act Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution is not clear on what kind of persons are considered as experts in their field and who has the authority to evaluate that someone is expert in his/her field.